Stochastic Analysis, Control, Optimization and Applications 1999
DOI: 10.1007/978-1-4612-1784-8_33
|View full text |Cite
|
Sign up to set email alerts
|

Critical Power for Asymptotic Connectivity in Wireless Networks

Abstract: In wireless data networks each transmitter's power needs to be high enough to reach the intended receivers, while generating minimum interference on other receivers sharing the same channel. In particular, if the nodes in the network are assumed to cooperate in routing each others' packets, as is the case in ad hoc wireless networks, each node should transmit with just enough power to guarantee connectivity in the network. Towards this end, we derive the critical power a node in the network needs to transmit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
786
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 780 publications
(800 citation statements)
references
References 7 publications
14
786
0
Order By: Relevance
“…In a 2-dimensional random geometric graph, n nodes are randomly assigned coordinates uniformly in unit square, and two nodes are connected with an edge when their Euclidean distance is less than or equal to a connectivity radius, r [6,7]. In [6] it is shown that if the connectivity radius scales as r con (n) = Θ( log n n ) then the network is connected with high probability. Throughout this paper when we refer to a random geometric graph, we mean one with the connectivity r con (n).…”
Section: Previous Work and Known Resultsmentioning
confidence: 99%
“…In a 2-dimensional random geometric graph, n nodes are randomly assigned coordinates uniformly in unit square, and two nodes are connected with an edge when their Euclidean distance is less than or equal to a connectivity radius, r [6,7]. In [6] it is shown that if the connectivity radius scales as r con (n) = Θ( log n n ) then the network is connected with high probability. Throughout this paper when we refer to a random geometric graph, we mean one with the connectivity r con (n).…”
Section: Previous Work and Known Resultsmentioning
confidence: 99%
“…Random geometric graphs are often used to model the one-hop connectivity in wireless networks, where the threshold γ can be viewed as a proxy to the communication range employed by wireless nodes; e.g., [27,33,34].…”
Section: Random Geometric Graphsmentioning
confidence: 99%
“…Reasonably, in the case R = 22m, a higher node density is required to reach this reachability. Detailed studies of critical density for wireless network connectivity can be found in [20], [21]. Here, we will focus on the comparison among different k-hop searching results.…”
Section: A Study Of Simple Geographic Greedy Routingmentioning
confidence: 99%